2013
DOI: 10.1016/j.jneuroling.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of subcortical structures in recited speech: Studies in Parkinson's disease

Abstract: The role of subcortical structures in language function is complex and dependent on language task, with studies increasingly showing subcortical involvement for the production of formulaic language, including recited speech. Individuals with Parkinson's disease (PD), with (n = 6) and without (n = 7) surgical treatment, deep brain stimulation (DBS), were compared to healthy adults (n = 14) to determine whether individuals with subcortical dysfunction produce more errors during a recitation speech task. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…It is noteworthy that despite the distinction of the pathophysiology of the diseases discussed, the functionality of the system is compromised, generating important communicative impact. Thus, it is possible to observe that, according to reports in the literature and the clinical characteristics presented by the patient described, regardless of the type of impairment, speech-language features tend to perform similarly as reported in findings in individuals with Parkinson's disease, and this an important marker for suspecting diseases that do not complete a typical clinical condition of this disease, but that indicate changes in the basal ganglia, such as Fahr's disease (12)(13)(14) . On the basis of these descriptions, one can highlight the importance of the speech-language professional in the accurate evaluation of stomatognathic functions.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It is noteworthy that despite the distinction of the pathophysiology of the diseases discussed, the functionality of the system is compromised, generating important communicative impact. Thus, it is possible to observe that, according to reports in the literature and the clinical characteristics presented by the patient described, regardless of the type of impairment, speech-language features tend to perform similarly as reported in findings in individuals with Parkinson's disease, and this an important marker for suspecting diseases that do not complete a typical clinical condition of this disease, but that indicate changes in the basal ganglia, such as Fahr's disease (12)(13)(14) . On the basis of these descriptions, one can highlight the importance of the speech-language professional in the accurate evaluation of stomatognathic functions.…”
Section: Discussionsupporting
confidence: 64%
“…In relation to the functions of the stomatognathic system, diseases that affect this region also affect the orofacial motor functions and the capacity of expressiveness of speech, in addition to vocal aspects, and lead to difficulties in conducting the food bolus because of the change in muscle tone. Among the most studied diseases that affect this system are Parkinson's disease, extensively studied in the Speech-Language Pathology and Audiology field, and, more recently, diseases that result in the degeneration and calcification of the region, such as Fahr's disease (1,12,13) . It is observed that the impairment of brain structures involved in the movement coordination process causes disability in performing combined motor functions, because the integration of motor information does not occur in an orderly manner (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Biber et al, 1999 , p. 132) It may not be surprising that the meaning of theticals has been described with reference to notions such as 'subjectifi cation' (cf. the component Attitudes of [ 6 ] For the contribution of subcortical structures to the production of overlearned linguistic material (e.g., recited speech), see Bridges, Van Lancker Sidtis, and Sidtis (2013).…”
Section: The Two Fr Ameworkmentioning
confidence: 99%
“…Further, there were clear cut effects of neurological impairment: left hemisphere damage was associated with a significantly greater proportion of words in formulaic language, while right hemisphere damage showed significantly less (Van Lancker and Postman, 2006). Performance data from the vertical dimension of the brain, comparing cortical (Alzheimer’s disease) with basal ganglia (Parkinson’s disease) impairment, revealed retention of formulaic language in the former and loss in the latter (Bridges and Van Lancker Sidtis, 2013; Bridges, Van Lancker Sidtis and Sidtis, 2013). These studies lead to a model of formulaic language as governed by a right hemisphere-subcortical system (See Van Lancker, 2014, for review).…”
Section: Introductionmentioning
confidence: 99%